Programa Escolas Bilingues de Fronteira : das generalizações do documento às especificidades da fronteira entre Foz do Iguaçu e Puerto Iguazu - Oliveira, Renata Alves de (Universidade Federal de São Carlos, 2011)
The purpose of this research comes from the interest in studying the Bilingual Border Schools Program PEBF, which aim is to promote the teacher s exchange between Brazil and Argentina, to teach Portuguese to Argentinean children and Spanish to Brazilian children in the border communities. Thus, was made an interpretative analysis of the document entitled Bilingual Border Schools Program Model of common teaching in border schools, from the development of a program for the intercultural education, emphasizing the Portuguese and Spanish teaching, established by the Ministry of Education, Science and Technology of Argentina (MECyT) and Ministry of Education of Brazil (MEC) and published in March, 2008, intending to investigate the generalization employed by the premise that Argentinean children show a reasonable level of Bilingualism , seemed that they understand the Portuguese well, on the other hand, the majority of Brazilian children is highly monolingual . Therefore, was tried to make a reflexive revaluation about the PEBF participant children s bilingualism development, having as a direction the conception of the program participant teachers reported on this document trying to comprehend how the children are represented in the official regulation of the program. After that, external data was collected in the pair-schools CAIC Adele Zanotto e Escuela Bilíngue n° 2 which belong to Foz do Iguaçu City PR in Brazil and Puerto Iguazu, Misiones in Argentina, respectively, with the intention of verify whether the document generalization is applicable to project participants from this region, which has distinct geographical formation than others twin cities of the program. At first, was realised that the definition of bilingualism isn t concrete enough and the Program development context shows characteristics very peculiar that must be considered for doesn t make much of a community in detriment to other based on apparent data. It was possible comprehend that the generalization in respect of the differences in the bilinguality levels of Brazilian and Argentineans students is not totally applicable to the students of the project in the Foz do Iguaçu and Puerto Iguazu area, once that all students, Brazilian and Argentinean, were evaluated by the same way, and the school community content from each country is historically composed differently. It was observed ,too, that the teachers reproduce the document speech, confirming the data that the Argentinean children develop the bilinguality easier due to a higher exposure to Portuguese, while Brazilian children are less exposed to Spanish, because of fluvial border between Foz do Iguaçu and Puerto Iguazu as well as a series of socioeconomic influences which aggregate bigger prestige to Portuguese in this area, revealing a adverse context for the bilinguality development for the Brazilian students. Hence, it was found that the social duty of languages in the Brazilian and Argentinean communities interferes directly on the participants performance of the project and, consequently, enforces the children s representation showed by documentation published in 2008.
Keywords: Língua espanhola; Brasil - fronteiras; Bilinguismo; PEBF; Border; Bilingualism; Bilingualility; PEBF; LINGUISTICA, LETRAS E ARTES::LINGUISTICA